Cyclin-Dependent Kinase 9 (CDK9) Inhibitor Atuveciclib Suppresses Intervertebral Disk Degeneration via the Inhibition of the NF-κB Signaling Pathway - Ni, Weiyu; Zhang, Feizhou; Zheng, Lin; Wang, Lili; Liang, Yi; Ding, Yuhong; Yik, Jasper H. N.; Haudenschild, Dominik R.; Fan, Shunwu; Hu, Ziang (Frontiers in Cell and Developmental Biology, 2020)
Intervertebral disc degeneration (IVDD) is mainly caused by an inflammatory response induced by various proinflammatory cytokines, such as interleukin (IL)-1β and tumor necrosis factor-α. Cyclin-dependent kinase 9 (CDK9) is a transcriptional regulator and potential therapeutic target for many diseases, especially in controlling the activation of primary inflammatory response genes. Our study aimed to investigate a highly selective CDK9 inhibitor, atuveciclib, which protects nucleus pulposus (NP) cells from proinflammatory stimuli-induced catabolic effects and apoptosis induction. The effects of atuveciclib were determined in human and rat NP cells treated with IL-1β in the presence or absence of atuveciclib or small interfering RNA target CDK9. In addition, rat intervertebral disc explants were used to determine the role of atuveciclib in extracellular matrix degradation. Results showed that CDK9 inhibition attenuated IVDD in the rat puncture model, as demonstrated by magnetic resonance imaging and immunohistochemistry. Taken together, CDK9 is a potential therapeutic target to prevent IVDD.